A corrosion-resistant coating for metal bipolar plate and preparation method thereof
Through multi-step chemical reaction, modified graphene and epoxy resin are prepared to form a corrosion-resistant coating, which solves the problem of corrosion-free metal bipolar plates in high-temperature and strong acid environments, and achieves excellent corrosion resistance, hydrophobicity, adhesion and high-temperature resistance.
Patent Information
- Application Number
- CN202411355617.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing metal bipolar plates are easily corroded in the high temperature and strong acid environment of proton exchange membrane fuel cells, affecting the conductivity and durability of the cells.
Modified graphene is prepared by multi-step chemical reaction, and combined with epoxy resin, and the corrosion-resistant coating is formed by electrochemical deposition and heat treatment. The coating forms an excellent conductive network and protective layer on the surface of the metal bipolar plate, improving its corrosion resistance and adhesion.
It significantly improves the corrosion resistance, hydrophobic performance, adhesion and high temperature resistance of metal bipolar plates, reduces contact resistance, and is suitable for high-temperature and strong acid environments.
Smart Images

Figure BDA0005063524650000121 
Figure BDA0005063524650000131
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal bipolar plates for fuel cells, and in particular relates to a corrosion-resistant coating for metal bipolar plates and a preparation method thereof. Background Art
[0002] Bipolar plates are key components of proton exchange membrane fuel cells (PEMFCs). They not only conduct electricity and separate gases, but also have an important impact on the overall performance and durability of the battery. Metal bipolar plates have been widely studied due to their cost-effectiveness and processing advantages, but they are susceptible to corrosion in the high temperature and strong acidic environment of PEMFCs, which affects the conductivity and durability of the battery. The coating technology of metal bipolar plates is the key to improving their performance. Studies have shown that the coatings of metal bipolar plates can be divided into metal coatings, non-metallic coatings and composite coatings. Among them, non-metallic coatings such as graphite-based coatings and conductive polymer coatings are simple to prepare and low in cost, becoming a hot topic for scientists.
[0003] The patent with application number CN202211617308.1 provides a method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate. A magnesium alloy with extremely low density is used as a substrate, and a corrosion-resistant coating is arranged on the surface of the substrate. The corrosion-resistant coating uses a conductive polymer such as polyaniline as a matrix material. Polyaniline has corrosion inhibition behavior and anion exchangeability. While protecting the underlying metal substrate, it can exchange anions with chloride ions in the corrosive environment to inhibit the penetration of corrosive anions. At the same time, by compounding adhesives and nano-oxides, the bonding force between the polyaniline coating and the magnesium alloy and the corrosion resistance of the coating are further improved. The preparation process of the invention is simple, the operation steps are few, and it is safe and environmentally friendly. Compared with existing metal materials such as aluminum, nickel, titanium and stainless steel, it can greatly reduce the weight of proton exchange membrane fuel cells; polyaniline-based coatings show great potential in the application of bipolar plate coatings for fuel cells due to their unique electrochemical properties and conductivity. However, the long-term corrosion resistance of polyaniline coatings in the high-temperature and strong acid environment of fuel cells still needs to be improved, which limits their large-scale application in fuel cells. The patent with application number CN202210281155.1 provides a metal bipolar plate for a fuel cell. The invention sequentially covers a first coating and a second coating on a metal substrate, wherein the first coating is a graphene layer with holes, and the second coating contains graphene oxide and polytetrafluoroethylene, and the holes are filled with graphene oxide and polytetrafluoroethylene. The graphene composite coating of the invention has the advantages of low price, good mechanical properties, corrosion resistance and excellent conductivity in the working environment of proton exchange membrane fuel cells. It can meet the use requirements of fuel cell bipolar plates and is suitable for mass production; polytetrafluoroethylene is a polymer material widely used in various industrial fields, and is well-known for its excellent chemical stability and heat resistance, but its strong chemical inertness and extremely low surface energy lead to poor adhesion of the polytetrafluoroethylene coating, which seriously limits its application in the coating field. Summary of the invention
[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a corrosion-resistant coating for metal bipolar plates and a preparation method thereof. The present invention sequentially utilizes epoxy ring-opening reaction, esterification reaction, hydrolysis polymerization reaction, and reduction reaction to prepare modified graphene, and then compounds the modified graphene and epoxy resin, and the metal bipolar plate coating prepared by electrochemical deposition and heat treatment has excellent contact resistance, corrosion resistance, hydrophobicity, adhesion, and high temperature resistance.
[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0006] A method for preparing a corrosion-resistant coating for a metal bipolar plate comprises the following steps:
[0007] Step S1, dispersing 3-aminopropyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide and boric acid in toluene, mixing evenly and raising the temperature to 60-70° C., reacting for 15-20 hours under stirring, cooling to room temperature, removing the solvent, purifying to obtain product 1;
[0008] Step S2, dispersing 3-quinoline-2-propionic acid in N,N-dimethylformamide, raising the temperature to 60-65° C., then sequentially adding the product 1 obtained in step S1 and p-toluenesulfonic acid, reacting for 4-7 hours under stirring conditions, cooling to room temperature, extracting, concentrating, and drying to obtain a silane modifier;
[0009] Step S3, ultrasonically dispersing graphene oxide in an ethanol aqueous solution, adding the silane modifier obtained in step S2, raising the temperature to 50-60° C. under stirring, adjusting the pH to 5-6, reacting for 3-5 hours, cooling to room temperature, separating the solid from the liquid, washing and drying the solid, and obtaining modified graphene oxide;
[0010] Step S4, ultrasonically dispersing the modified graphene oxide obtained in step S3 in deionized water, adding hydroiodic acid, heating to 80-90° C. under stirring, reacting for 3-4 hours, cooling to room temperature, separating the solid from the liquid, washing and drying the solid to obtain the modified graphene;
[0011] Step S5, ultrasonically dispersing the modified graphene obtained in step S4 in deionized water to obtain a modified graphene dispersion; dispersing glacial acetic acid in deionized water, mixing evenly, then adding epoxy resin, stirring at room temperature for 1-2 hours, and standing to obtain an activated epoxy resin; adding the modified graphene dispersion to the activated epoxy resin, stirring at room temperature for 2-4 hours, and standing in a magnetic field to obtain an electrolyte solution;
[0012] Step S6: placing the pretreated metal bipolar plate, the reference electrode and the auxiliary electrode in an electrolyte solution, connecting them through a three-electrode system, performing electrochemical deposition using cyclic voltammetry, and then heat treating them at 170-190° C. for 20-40 min to form a corrosion-resistant coating on the surface of the metal bipolar plate.
[0013] As a new type of two-dimensional carbon nanomaterial, graphene has been widely studied for enhancing the performance of epoxy resin-based composites due to its unique physical and chemical properties, such as high electrical conductivity, high thermal conductivity and excellent mechanical properties. Epoxy resin is a thermosetting plastic with good mechanical properties, chemical stability and electrical insulation, but its poor heat resistance and high brittleness limit its application in high-performance fields. The addition of graphene and its derivatives provides new possibilities for epoxy resin-based composites in high-end applications by improving the electrical conductivity, thermal conductivity and mechanical properties of epoxy resin. However, the compatibility of conductive fillers with resins is affected by the surface functional groups of the raw materials, which directly affects the dispersion uniformity of the conductive fillers and the interface properties of the conductive fillers / resins. The present invention uses 3-aminopropyltriethoxysilane and 3-(perfluoro-n-hexyl)propylene oxide as starting materials, and an epoxy ring-opening reaction occurs under the catalysis of boric acid to obtain product 1; the product 1 contains a hydroxyl group in its structure, and an esterification reaction occurs with 3-quinoline-2-propionic acid under the catalysis of p-toluenesulfonic acid to obtain a silane modifier; the graphene oxide is modified by the silane modifier, and a plurality of organic functional groups are introduced on the surface of the graphene oxide particles by means of a hydrolysis condensation reaction to obtain modified graphene oxide; the modified graphene oxide is then subjected to a reduction reaction to obtain modified graphene; the modified graphene and an epoxy resin are then compounded to obtain an electrolyte solution; and finally, a pretreated metal bipolar plate, a reference electrode and an auxiliary electrode are placed in the electrolyte solution, and a corrosion-resistant coating is formed on the surface of the metal bipolar plate after electrochemical deposition and heat treatment.
[0014] In order to obtain a functionalized and directionally modified metal bipolar plate surface coating, the molar ratio of 3-aminopropyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid in step S1 is 1:0.95-1.05:0.15-0.25, and the mass volume ratio of 3-aminopropyltriethoxysilane to toluene is 0.13-0.22 g / mL; the mass ratio of 3-quinoline-2-propionic acid, product 1, and p-toluenesulfonic acid in step S2 is 0 .5:0.8-1.0:0.05-0.08, the mass volume ratio of the 3-quinoline-2-propionic acid to N,N-dimethylformamide is 0.15-0.20 g / mL; the mass ratio of the graphene oxide to the silane modifier in step S3 is 1:0.5-0.8, the amount of graphene oxide added to the ethanol aqueous solution is 0.021-0.027 g / mL, and the mass fraction of ethanol in the ethanol aqueous solution is 80-90%; the mass ratio of the graphene oxide to the silane modifier in step S4 is 1:0.5-0.8, the amount of the graphene oxide added to the ethanol aqueous solution is 0.021-0.027 g / mL, and the mass fraction of ethanol in the ethanol aqueous solution is 80-90%; The mass ratio of the modified graphene oxide, deionized water, and hydroiodic acid is 1:20-30:1.5-2.5; the mass ratio of the modified graphene to deionized water in the preparation process of the modified graphene dispersion in step S5 is 0.008-0.012:100, the mass ratio of glacial acetic acid, deionized water, and epoxy resin in the preparation process of the activated epoxy resin is 5:300-400:60-70, and the mass ratio of the modified graphene dispersion to the activated epoxy resin in the preparation process of the electrolyte solution in step S5 is 0.8-1.0:1; the pretreatment (hydroxylation treatment) process of the metal bipolar plate in step S6 is: ultrasonically cleaning the metal bipolar plate in acetone, anhydrous ethanol, and deionized water respectively, placing it in a mixed solution of concentrated sulfuric acid and hydrogen peroxide after drying, reacting at 80-100°C for 1-3h, taking it out and drying it; the metal bipolar plate in step S6 is made of 316L stainless steel.
[0015] The corrosion-resistant coating for metal bipolar plates is prepared by the above method.
[0016] The present invention has the following beneficial effects:
[0017] The present invention utilizes multi-step chemical reactions to prepare modified graphene, and introduces quinoline rings, fluorine, siloxane, and alkyl chains on the surface of graphene particles. Fluorine is the element with the highest electronegativity, and it can form a very strong covalent bond with carbon. This bond is difficult to break. Therefore, fluorine compounds usually have good chemical stability, are not easy to participate in electrochemical reactions, and exhibit excellent corrosion resistance in electrochemical corrosion environments; siloxane can form chemical bonds or physical interactions with polar groups on the surface of materials, and thus can form good adhesion with the surfaces of various materials (such as glass, metal, plastic, and ceramics). The synergistic effect of siloxane and epoxy resin can significantly improve the bonding properties of epoxy resin, thereby significantly improving the adhesion of the composite coating material on the surface of metal bipolar plates; the combination of fluorine and siloxane can also improve the composite coating material at high The quinoline ring has a stable conjugated system, and the π-π stacking effect between the quinoline rings can enhance the interaction between molecules, making it difficult to decompose at high temperatures, thereby making the product exhibit excellent heat resistance; the introduction of a variety of organic groups in the modified graphene structure can also improve the dispersibility and compatibility of inorganic particles in epoxy resin materials, effectively play the reinforcing role of modified graphene, compound the modified graphene and epoxy resin, and perform electrochemical deposition under the action of a magnetic field. After heat treatment, through mutual cross-linking, an excellent conductive network and protective layer can be formed on the surface of the metal bipolar plate, and the contact resistance of the metal bipolar plate can be significantly reduced.
[0018] The metal bipolar plate coating provided by the present invention has excellent contact resistance, corrosion resistance, hydrophobicity, adhesion and high temperature resistance. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application. 3-(Perfluoro-n-hexyl)propylene oxide, CAS No. 38565-52-5; graphene oxide, thickness 0.6-1.2nm, diameter 0.8-2μm, purity 99%, purchased from Guangzhou Hongwu Materials Technology Co., Ltd.; epoxy resin, model E-51, brand Baling Petrochemical, viscosity 11000-14000 (mPa·s).
[0020] Example 1
[0021] A method for preparing a corrosion-resistant coating for a metal bipolar plate comprises the following steps:
[0022] Step S1, dispersing 3-aminopropyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid in toluene, mixing well, raising the temperature to 65° C., reacting for 17 hours under stirring, cooling to room temperature, distilling off toluene under reduced pressure, and then purifying by column chromatography (petroleum ether / ethyl acetate) to obtain product 1; wherein the molar ratio of 3-aminopropyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid is 1:1:0.2, and the mass volume ratio of 3-aminopropyltriethoxysilane to toluene is 0.18 g / mL;
[0023] Step S2, dispersing 3-quinoline-2-propionic acid in N,N-dimethylformamide, raising the temperature to 63°C, and then sequentially adding the product 1 obtained in step S1 and p-toluenesulfonic acid, reacting for 6 hours under stirring, cooling to room temperature, and then adding deionized water and ethyl acetate for extraction, taking the organic phase and concentrating it, and drying it in a vacuum drying oven at 60°C for 12 hours to obtain a silane modifier; wherein the mass ratio of 3-quinoline-2-propionic acid, product 1, and p-toluenesulfonic acid is 0.5:0.9:0.07, the mass volume ratio of 3-quinoline-2-propionic acid to N,N-dimethylformamide is 0.17 g / mL, and the volume ratio of N,N-dimethylformamide, deionized water, and ethyl acetate is 1:1:2;
[0024] Step S3, ultrasonically dispersing graphene oxide in an ethanol aqueous solution, adding the silane modifier obtained in step S2, raising the temperature to 55°C under stirring, adjusting the pH to 5-6 with 2 mol / L hydrochloric acid, reacting for 4 hours, cooling to room temperature, separating the solid and the liquid, taking the solid, rinsing with water, and drying in a vacuum drying oven at 65°C for 12 hours to obtain modified graphene oxide; wherein the mass ratio of graphene oxide to the silane modifier is 1:0.6, the amount of graphene oxide added to the ethanol aqueous solution is 0.025 g / mL, the mass fraction of ethanol in the ethanol aqueous solution is 85%, the ultrasonic power of the ultrasonic dispersion is 300 W, and the ultrasonic time is 10 min;
[0025] Step S4, ultrasonically dispersing the modified graphene oxide obtained in step S3 in deionized water, adding hydroiodic acid, heating to 85°C under stirring, reacting for 3.5 hours, cooling to room temperature, separating the solid and the liquid, taking the solid, rinsing with water, and drying in a vacuum drying oven at 65°C for 24 hours to obtain modified graphene; wherein the mass ratio of modified graphene oxide, deionized water, and hydroiodic acid is 1:25:2, the ultrasonic power of ultrasonic dispersion is 400W, and the ultrasonic time is 15min;
[0026] Step S5, ultrasonically dispersing the modified graphene obtained in step S4 in deionized water, with an ultrasonic power of 400 W and an ultrasonic time of 15 min to obtain a modified graphene dispersion; dispersing glacial acetic acid in deionized water, mixing well, and then adding epoxy resin, stirring at room temperature for 1.5 hours, and letting it stand naturally for 12 hours to obtain an activated epoxy resin; adding the modified graphene dispersion to the activated epoxy resin, stirring at room temperature for 3 hours, placing it in a 15T magnetic field and letting it stand for 12 hours to obtain an electrolyte solution; wherein, in the preparation process of the modified graphene dispersion, the mass ratio of the modified graphene to the deionized water is 0.01:100, the mass ratio of the glacial acetic acid, the deionized water, and the epoxy resin in the preparation process of the activated epoxy resin is 5:350:65, and the mass ratio of the modified graphene dispersion to the activated epoxy resin in the preparation process of the electrolyte solution is 0.9:1;
[0027] Step S6, placing the pretreated metal bipolar plate, the reference electrode and the auxiliary electrode in an electrolyte solution, connecting them through a three-electrode system, in a magnetic field of 15T, with the metal bipolar plate facing the magnetic field, electrochemical deposition is performed using cyclic voltammetry, and then heat-treated at 180°C for 30 minutes to form a corrosion-resistant coating on the surface of the metal bipolar plate; wherein the pretreatment process of the metal bipolar plate is: ultrasonically cleaning the metal bipolar plate in acetone, anhydrous ethanol and deionized water respectively, and ultrasonic power The power was 800W, the ultrasonic time was 5min, and after natural drying for 24h, it was placed in a mixed solution of concentrated sulfuric acid and hydrogen peroxide, the concentrated sulfuric acid concentration was 98%, the volume ratio of concentrated sulfuric acid to hydrogen peroxide was 75:25, and the reaction was carried out at 90°C for 2h, and the product was obtained after natural drying; the metal bipolar plate was made of 316L stainless steel; the reference electrode was a calomel electrode; the auxiliary electrode was a platinum electrode; the scanning potential was -200-1200mV, the scanning speed was 30mV / s, and the number of cycles was 20 times.
[0028] Example 2
[0029] A method for preparing a corrosion-resistant coating for a metal bipolar plate comprises the following steps:
[0030] Step S1, dispersing 3-aminopropyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid in toluene, mixing well, raising the temperature to 60° C., reacting for 20 hours under stirring, cooling to room temperature, distilling under reduced pressure to remove toluene, and then purifying by column chromatography (petroleum ether / ethyl acetate) to obtain product 1; wherein the molar ratio of 3-aminopropyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid is 1:1.05:0.25, and the mass volume ratio of 3-aminopropyltriethoxysilane to toluene is 0.13 g / mL;
[0031] Step S2, dispersing 3-quinoline-2-propionic acid in N,N-dimethylformamide, raising the temperature to 60°C, and then sequentially adding the product 1 obtained in step S1 and p-toluenesulfonic acid, reacting for 7 hours under stirring, cooling to room temperature, and then adding deionized water and ethyl acetate for extraction, taking the organic phase and concentrating it, and drying it in a vacuum drying oven at 60°C for 12 hours to obtain a silane modifier; wherein the mass ratio of 3-quinoline-2-propionic acid, product 1, and p-toluenesulfonic acid is 0.5:1:0.08, the mass volume ratio of 3-quinoline-2-propionic acid to N,N-dimethylformamide is 0.15 g / mL, and the volume ratio of N,N-dimethylformamide, deionized water, and ethyl acetate is 1:1:2;
[0032] Step S3, ultrasonically dispersing graphene oxide in an ethanol aqueous solution, adding the silane modifier obtained in step S2, raising the temperature to 50°C under stirring, adjusting the pH to 5-6 with 2 mol / L hydrochloric acid, reacting for 5 hours, cooling to room temperature, separating the solid and the liquid, taking the solid, rinsing with water, and drying in a vacuum drying oven at 65°C for 12 hours to obtain modified graphene oxide; wherein the mass ratio of graphene oxide to the silane modifier is 1:0.8, the amount of graphene oxide added to the ethanol aqueous solution is 0.027 g / mL, the mass fraction of ethanol in the ethanol aqueous solution is 90%, the ultrasonic power of the ultrasonic dispersion is 300 W, and the ultrasonic time is 10 min;
[0033] Step S4, ultrasonically dispersing the modified graphene oxide obtained in step S3 in deionized water, adding hydroiodic acid, heating to 80°C under stirring, reacting for 4 hours, cooling to room temperature, separating the solid and the liquid, taking the solid, rinsing with water, and drying in a vacuum drying oven at 65°C for 24 hours to obtain modified graphene; wherein the mass ratio of modified graphene oxide, deionized water, and hydroiodic acid is 1:30:2.5, the ultrasonic power of ultrasonic dispersion is 400W, and the ultrasonic time is 15min;
[0034] Step S5, ultrasonically dispersing the modified graphene obtained in step S4 in deionized water, with an ultrasonic power of 400 W and an ultrasonic time of 15 min to obtain a modified graphene dispersion; dispersing glacial acetic acid in deionized water, mixing well, adding epoxy resin, stirring at room temperature for 1 hour, and letting stand naturally for 12 hours to obtain an activated epoxy resin; adding the modified graphene dispersion to the activated epoxy resin, stirring at room temperature for 2 hours, placing in a 15T magnetic field and letting stand for 12 hours to obtain an electrolyte solution; wherein, in the preparation process of the modified graphene dispersion, the mass ratio of the modified graphene to the deionized water is 0.012:100, the mass ratio of the glacial acetic acid, the deionized water, and the epoxy resin in the preparation process of the activated epoxy resin is 5:400:70, and the mass ratio of the modified graphene dispersion to the activated epoxy resin in the preparation process of the electrolyte solution is 1:1;
[0035] Step S6, placing the pretreated metal bipolar plate, the reference electrode and the auxiliary electrode in an electrolyte solution, connecting them through a three-electrode system, in a magnetic field of 15T, with the metal bipolar plate facing the magnetic field, electrochemical deposition is performed using cyclic voltammetry, and then heat-treated at 170°C for 40 minutes to form a corrosion-resistant coating on the surface of the metal bipolar plate; wherein the pretreatment process of the metal bipolar plate is: ultrasonically cleaning the metal bipolar plate in acetone, anhydrous ethanol and deionized water respectively, and ultrasonic power The power was 800W, the ultrasonic time was 5min, and after natural drying for 24h, it was placed in a mixed solution of concentrated sulfuric acid and hydrogen peroxide, the concentration of concentrated sulfuric acid was 98%, the volume ratio of concentrated sulfuric acid to hydrogen peroxide was 75:25, and the reaction was carried out at 80°C for 3h, and the product was obtained after natural drying; the metal bipolar plate was made of 316L stainless steel; the reference electrode was a calomel electrode; the auxiliary electrode was a platinum electrode; the scanning potential was -200-1200mV, the scanning speed was 30mV / s, and the number of cycles was 20 times.
[0036] Example 3
[0037] A method for preparing a corrosion-resistant coating for a metal bipolar plate comprises the following steps:
[0038] Step S1, dispersing 3-aminopropyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid in toluene, mixing well, raising the temperature to 70°C, reacting for 15 hours under stirring, cooling to room temperature, distilling under reduced pressure to remove toluene, and then purifying by column chromatography (petroleum ether / ethyl acetate) to obtain product 1; wherein the molar ratio of 3-aminopropyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid is 1:0.95:0.15, and the mass volume ratio of 3-aminopropyltriethoxysilane to toluene is 0.22 g / mL;
[0039] Step S2, dispersing 3-quinoline-2-propionic acid in N,N-dimethylformamide, raising the temperature to 65°C, and then sequentially adding the product 1 obtained in step S1 and p-toluenesulfonic acid, reacting for 4 hours under stirring, cooling to room temperature, and then adding deionized water and ethyl acetate for extraction, taking the organic phase and concentrating it, and drying it in a vacuum drying oven at 60°C for 12 hours to obtain a silane modifier; wherein the mass ratio of 3-quinoline-2-propionic acid, product 1, and p-toluenesulfonic acid is 0.5:0.8:0.05, the mass volume ratio of 3-quinoline-2-propionic acid to N,N-dimethylformamide is 0.2 g / mL, and the volume ratio of N,N-dimethylformamide, deionized water, and ethyl acetate is 1:1:2;
[0040] Step S3, ultrasonically dispersing graphene oxide in an ethanol aqueous solution, adding the silane modifier obtained in step S2, raising the temperature to 60°C under stirring, adjusting the pH to 5-6 with 2 mol / L hydrochloric acid, reacting for 3 hours, cooling to room temperature, separating the solid and the liquid, taking the solid, rinsing with water, and drying in a vacuum drying oven at 65°C for 12 hours to obtain modified graphene oxide; wherein the mass ratio of graphene oxide to the silane modifier is 1:0.5, the amount of graphene oxide added to the ethanol aqueous solution is 0.021 g / mL, the mass fraction of ethanol in the ethanol aqueous solution is 80%, the ultrasonic power of the ultrasonic dispersion is 300 W, and the ultrasonic time is 10 min;
[0041] Step S4, ultrasonically dispersing the modified graphene oxide obtained in step S3 in deionized water, adding hydroiodic acid, heating to 90° C. under stirring, reacting for 3 h, cooling to room temperature, separating the solid and the liquid, taking the solid, rinsing with water, and drying in a vacuum drying oven at 65° C. for 24 h to obtain modified graphene; wherein the mass ratio of modified graphene oxide, deionized water, and hydroiodic acid is 1:20:1.5, the ultrasonic power of ultrasonic dispersion is 400 W, and the ultrasonic time is 15 min;
[0042] Step S5, ultrasonically dispersing the modified graphene obtained in step S4 in deionized water, with an ultrasonic power of 400 W and an ultrasonic time of 15 min to obtain a modified graphene dispersion; dispersing glacial acetic acid in deionized water, adding epoxy resin after mixing evenly, stirring at room temperature for 2 hours, and letting it stand naturally for 12 hours to obtain an activated epoxy resin; adding the modified graphene dispersion to the activated epoxy resin, stirring at room temperature for 4 hours, placing it in a 15T magnetic field and letting it stand for 12 hours to obtain an electrolyte solution; wherein, in the preparation process of the modified graphene dispersion, the mass ratio of the modified graphene to the deionized water is 0.008:100, the mass ratio of the glacial acetic acid, the deionized water, and the epoxy resin in the preparation process of the activated epoxy resin is 5:300:60, and the mass ratio of the modified graphene dispersion to the activated epoxy resin in the preparation process of the electrolyte solution is 0.8:1;
[0043] Step S6, placing the pretreated metal bipolar plate, the reference electrode and the auxiliary electrode in an electrolyte solution, connecting them through a three-electrode system, in a magnetic field of 15T, with the metal bipolar plate facing the magnetic field, electrochemical deposition is performed using cyclic voltammetry, and then heat-treated at 190°C for 20 minutes to form a corrosion-resistant coating on the surface of the metal bipolar plate; wherein the pretreatment process of the metal bipolar plate is: ultrasonically cleaning the metal bipolar plate in acetone, anhydrous ethanol and deionized water respectively, and ultrasonic power The rate was 800W, the ultrasonic time was 5min, and after natural drying for 24h, the mixture was placed in a mixed solution of concentrated sulfuric acid and hydrogen peroxide, the concentration of concentrated sulfuric acid was 98%, the volume ratio of concentrated sulfuric acid to hydrogen peroxide was 75:25, and the mixture was reacted at 100°C for 1h, and the mixture was taken out and dried naturally to obtain the metal bipolar plate. The metal bipolar plate was made of 316L stainless steel. The reference electrode was a calomel electrode. The auxiliary electrode was a platinum electrode. The scanning potential was -200-1200mV, the scanning speed was 30mV / s, and the number of cycles was 20.
[0044] Comparative Example 1
[0045] A method for preparing a corrosion-resistant coating for a metal bipolar plate comprises the following steps:
[0046] Step S1, dispersing 3-aminopropyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid in toluene, mixing well, raising the temperature to 65° C., reacting for 17 hours under stirring, cooling to room temperature, distilling under reduced pressure to remove toluene, and then purifying by column chromatography (petroleum ether / ethyl acetate) to obtain a silane modifier; wherein the molar ratio of 3-aminopropyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide, and boric acid is 1:1:0.2, and the mass volume ratio of 3-aminopropyltriethoxysilane to toluene is 0.18 g / mL;
[0047] Step S2, ultrasonically dispersing graphene oxide in an ethanol aqueous solution, adding the silane modifier obtained in step S1, raising the temperature to 55°C under stirring, adjusting the pH to 5-6 with 2 mol / L hydrochloric acid, reacting for 4 hours, cooling to room temperature, separating the solid and the liquid, taking the solid, rinsing with water, and drying in a vacuum drying oven at 65°C for 12 hours to obtain modified graphene oxide; wherein the mass ratio of graphene oxide to the silane modifier is 1:0.55, the amount of graphene oxide added to the ethanol aqueous solution is 0.025 g / mL, the mass fraction of ethanol in the ethanol aqueous solution is 85%, the ultrasonic power of the ultrasonic dispersion is 300 W, and the ultrasonic time is 10 min;
[0048] Step S3, ultrasonically dispersing the modified graphene oxide obtained in step S2 in deionized water, adding hydroiodic acid, heating to 85°C under stirring, reacting for 3.5 hours, cooling to room temperature, separating the solid and the liquid, taking the solid, rinsing with water, and drying in a vacuum drying oven at 65°C for 24 hours to obtain modified graphene; wherein the mass ratio of modified graphene oxide, deionized water, and hydroiodic acid is 1:25:2, the ultrasonic power of ultrasonic dispersion is 400W, and the ultrasonic time is 15min;
[0049] Step S4, ultrasonically dispersing the modified graphene obtained in step S3 in deionized water, with an ultrasonic power of 400 W and an ultrasonic time of 15 min to obtain a modified graphene dispersion; dispersing glacial acetic acid in deionized water, adding epoxy resin after mixing evenly, stirring at room temperature for 1.5 hours, and letting it stand naturally for 12 hours to obtain an activated epoxy resin; adding the modified graphene dispersion to the activated epoxy resin, stirring at room temperature for 3 hours, placing it in a 15T magnetic field and letting it stand for 12 hours to obtain an electrolyte solution; wherein, in the preparation process of the modified graphene dispersion, the mass ratio of the modified graphene to the deionized water is 0.01:100, the mass ratio of the glacial acetic acid, the deionized water, and the epoxy resin in the preparation process of the activated epoxy resin is 5:350:65, and the mass ratio of the modified graphene dispersion to the activated epoxy resin in the preparation process of the electrolyte solution is 0.9:1;
[0050] Step S5, placing the pretreated metal bipolar plate, the reference electrode and the auxiliary electrode in an electrolyte solution, connecting them through a three-electrode system, in a magnetic field of 15T, with the metal bipolar plate facing the magnetic field, electrochemical deposition is performed using cyclic voltammetry, and then heat-treated at 180°C for 30 minutes to form a corrosion-resistant coating on the surface of the metal bipolar plate; wherein the pretreatment process of the metal bipolar plate is: ultrasonically cleaning the metal bipolar plate in acetone, anhydrous ethanol and deionized water respectively, and ultrasonic power The power was 800W, the ultrasonic time was 5min, and after natural drying for 24h, it was placed in a mixed solution of concentrated sulfuric acid and hydrogen peroxide, the concentrated sulfuric acid concentration was 98%, the volume ratio of concentrated sulfuric acid to hydrogen peroxide was 75:25, and the reaction was carried out at 90°C for 2h, and the product was obtained after natural drying; the metal bipolar plate was made of 316L stainless steel; the reference electrode was a calomel electrode; the auxiliary electrode was a platinum electrode; the scanning potential was -200-1200mV, the scanning speed was 30mV / s, and the number of cycles was 20 times.
[0051] Comparative Example 2
[0052] A method for preparing a corrosion-resistant coating for a metal bipolar plate comprises the following steps:
[0053] Step S1, ultrasonically dispersing graphene oxide in an ethanol aqueous solution, adding 3-aminopropyltriethoxysilane, raising the temperature to 55°C under stirring, adjusting the pH to 5-6 with 2 mol / L hydrochloric acid, reacting for 4 hours, cooling to room temperature, separating the solid and the liquid, taking the solid, rinsing with water, and drying in a vacuum drying oven at 65°C for 12 hours to obtain modified graphene oxide; wherein the mass ratio of graphene oxide to 3-aminopropyltriethoxysilane is 1:0.5, the amount of graphene oxide added to the ethanol aqueous solution is 0.025 g / mL, the mass fraction of ethanol in the ethanol aqueous solution is 85%, the ultrasonic power of ultrasonic dispersion is 300 W, and the ultrasonic time is 10 min;
[0054] Step S2, ultrasonically dispersing the modified graphene oxide obtained in step S1 in deionized water, adding hydroiodic acid, heating to 85°C under stirring, reacting for 3.5 hours, cooling to room temperature, separating the solid and the liquid, taking the solid, rinsing with water, and drying in a vacuum drying oven at 65°C for 24 hours to obtain modified graphene; wherein the mass ratio of modified graphene oxide, deionized water, and hydroiodic acid is 1:25:2, the ultrasonic power of ultrasonic dispersion is 400W, and the ultrasonic time is 15min;
[0055] Step S3, ultrasonically dispersing the modified graphene obtained in step S2 in deionized water, with an ultrasonic power of 400 W and an ultrasonic time of 15 min to obtain a modified graphene dispersion; dispersing glacial acetic acid in deionized water, adding epoxy resin after mixing evenly, stirring at room temperature for 1.5 hours, and letting it stand naturally for 12 hours to obtain an activated epoxy resin; adding the modified graphene dispersion to the activated epoxy resin, stirring at room temperature for 3 hours, placing it in a 15T magnetic field and letting it stand for 12 hours to obtain an electrolyte solution; wherein, in the preparation process of the modified graphene dispersion, the mass ratio of the modified graphene to the deionized water is 0.01:100, the mass ratio of the glacial acetic acid, the deionized water, and the epoxy resin in the preparation process of the activated epoxy resin is 5:350:65, and the mass ratio of the modified graphene dispersion to the activated epoxy resin in the preparation process of the electrolyte solution is 0.9:1;
[0056] Step S4, placing the pretreated metal bipolar plate, the reference electrode and the auxiliary electrode in an electrolyte solution, connecting them through a three-electrode system, in a magnetic field of 15T, with the metal bipolar plate facing the magnetic field, electrochemical deposition is performed using cyclic voltammetry, and then heat-treated at 180°C for 30 minutes to form a corrosion-resistant coating on the surface of the metal bipolar plate; wherein the pretreatment process of the metal bipolar plate is: ultrasonically cleaning the metal bipolar plate in acetone, anhydrous ethanol and deionized water respectively, and ultrasonic power The power was 800W, the ultrasonic time was 5min, and after natural drying for 24h, it was placed in a mixed solution of concentrated sulfuric acid and hydrogen peroxide, the concentrated sulfuric acid concentration was 98%, the volume ratio of concentrated sulfuric acid to hydrogen peroxide was 75:25, and the reaction was carried out at 90°C for 2h, and the product was obtained after natural drying; the metal bipolar plate was made of 316L stainless steel; the reference electrode was a calomel electrode; the auxiliary electrode was a platinum electrode; the scanning potential was -200-1200mV, the scanning speed was 30mV / s, and the number of cycles was 20 times.
[0057] Relevant performance tests were performed on the corrosion-resistant coatings for metal bipolar plates prepared in Examples 1-3 and Comparative Examples 1-2. The contact resistance and corrosion current density tests were carried out in accordance with GB / T20042.6-2011 "Proton Exchange Membrane Fuel Cell Part 6: Test Method for Bipolar Plate Characteristics". The contact resistance test pressure was 1.4 MPa, and the corrosion current density test was measured using a three-electrode electrochemical test system. The solution was 0.5 M H2SO4 + 5 ppm HF solution, the temperature was 80 ° C, and the operating voltage was 0.6 V; the hydrophobic performance test was carried out using a KRUSSDSA100 contact angle meter, and the amount of water dripped each time was 10 μL; the adhesion performance test was carried out in accordance with GB / T9286-2021 "Paint and Varnish Scratch Test" with a scratch spacing of 1 mm; the high temperature resistance test was carried out in accordance with GB / T1735-2009 "Determination of Heat Resistance of Paints and Varnishes". The sample was placed at a temperature of 280 ° C for 4 hours and the sample state was observed; the above tests were carried out three times and the average value was taken. The test results are shown in Table 1. It can be seen from Table 1 that the contact resistance, corrosion resistance, hydrophobicity and high temperature resistance of the corrosion-resistant coatings prepared in Examples 1-3 are significantly better than those in Comparative Examples 1-2; the corrosion current density of the corrosion-resistant coatings prepared in Examples 1-3 is lower than 0.24 μA / cm 2 , in line with DOE2020 bipolar plate performance requirements (<1μA / cm 2 ).
[0058] Table 1 Corrosion resistant coating performance test results for metal bipolar plates
[0059]
[0060]
[0061] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a corrosion-resistant coating for a metal bipolar plate, characterized in that: The following steps are involved: Step S1, dispersing 3-aminopropyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide and boric acid in toluene, mixing evenly and raising the temperature to 60-70° C., reacting for 15-20 hours under stirring, cooling to room temperature, removing the solvent, purifying to obtain product 1; Step S2, dispersing 3-quinoline-2-propionic acid in N,N-dimethylformamide, raising the temperature to 60-65° C., then sequentially adding the product 1 obtained in step S1 and p-toluenesulfonic acid, reacting for 4-7 hours under stirring conditions, cooling to room temperature, extracting, concentrating, and drying to obtain a silane modifier; Step S3, ultrasonically dispersing graphene oxide in an ethanol aqueous solution, adding the silane modifier obtained in step S2, raising the temperature to 50-60° C. under stirring, adjusting the pH to 5-6, reacting for 3-5 hours, cooling to room temperature, separating the solid from the liquid, washing and drying the solid, and obtaining modified graphene oxide; Step S4, ultrasonically dispersing the modified graphene oxide obtained in step S3 in deionized water, adding hydroiodic acid, heating to 80-90° C. under stirring, reacting for 3-4 hours, cooling to room temperature, separating the solid from the liquid, washing and drying the solid to obtain the modified graphene; Step S5, ultrasonically dispersing the modified graphene obtained in step S4 in deionized water to obtain a modified graphene dispersion; dispersing glacial acetic acid in deionized water, mixing evenly, then adding epoxy resin, stirring at room temperature for 1-2 hours, and standing to obtain an activated epoxy resin; adding the modified graphene dispersion to the activated epoxy resin, stirring at room temperature for 2-4 hours, and standing in a magnetic field to obtain an electrolyte solution; Step S6: placing the pretreated metal bipolar plate, the reference electrode and the auxiliary electrode in an electrolyte solution, connecting them through a three-electrode system, performing electrochemical deposition using cyclic voltammetry, and then heat treating them at 170-190° C. for 20-40 min to form a corrosion-resistant coating on the surface of the metal bipolar plate.
2. The method for preparing a corrosion-resistant coating for a metal bipolar plate according to claim 1, characterized in that: The molar ratio of 3-aminopropyltriethoxysilane, 3-(perfluoro-n-hexyl)propylene oxide and boric acid in step S1 is 1:0.95-1.05:0.15-0.25, and the mass volume ratio of 3-aminopropyltriethoxysilane to toluene is 0.13-0.22 g / mL.
3. The method for preparing a corrosion-resistant coating for a metal bipolar plate according to claim 1, characterized in that: The mass ratio of 3-quinoline-2-propionic acid, product 1, and p-toluenesulfonic acid in step S2 is 0.5:0.8-1.0:0.05-0.08, and the mass volume ratio of 3-quinoline-2-propionic acid to N,N-dimethylformamide is 0.15-0.20 g / mL.
4. The method for preparing a corrosion-resistant coating for a metal bipolar plate according to claim 1, characterized in that: In step S3, the mass ratio of graphene oxide to silane modifier is 1:0.5-0.8, the amount of graphene oxide added to the ethanol aqueous solution is 0.021-0.027 g / mL, and the mass fraction of ethanol in the ethanol aqueous solution is 80-90%.
5. The method for preparing a corrosion-resistant coating for a metal bipolar plate according to claim 1, characterized in that: The mass ratio of the modified graphene oxide, deionized water and hydroiodic acid in step S4 is 1:20-30:1.5-2.
5.
6. The method for preparing a corrosion-resistant coating for a metal bipolar plate according to claim 1, characterized in that: In the process of preparing the modified graphene dispersion in step S5, the mass ratio of modified graphene to deionized water is 0.008-0.012:100, and the mass ratio of glacial acetic acid, deionized water, and epoxy resin in the process of preparing the activated epoxy resin is 5:300-400:60-70.
7. The method for preparing a corrosion-resistant coating for a metal bipolar plate according to claim 1, characterized in that: In the electrolyte solution preparation process in step S5, the mass ratio of the modified graphene dispersion to the activated epoxy resin is 0.8-1.0:
1.
8. The method for preparing a corrosion-resistant coating for a metal bipolar plate according to claim 1, characterized in that: The pretreatment process of the metal bipolar plate in step S6 is: ultrasonically clean the metal bipolar plate in acetone, anhydrous ethanol, and deionized water respectively, place it in a mixed solution of concentrated sulfuric acid and hydrogen peroxide after drying, react at 80-100° C. for 1-3 hours, take it out and dry it.
9. The method for preparing a corrosion-resistant coating for a metal bipolar plate according to claim 1, characterized in that: The metal bipolar plate in step S6 is made of 316L stainless steel.
10. A corrosion-resistant coating for a metal bipolar plate, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Metal bipolar plate of fuel cell and preparation method of metal bipolar plate
CN114665102A
Preparation method and application of conductive anti-corrosion coating for magnesium alloy bipolar plate
CN116239906B
Preparation method of dispersible silane functionalized graphene
CN102351174A
Preparation method of high-thermal-conductivity self-supporting vertically oriented graphene film
CN113148986A